Investigating the immediate and delayed effects of multiple-reading strategy instruction in primary EFL classrooms. (February 2016) - Manoli, Polyxeni; Papadopoulou, Maria; Metallidou, Panagiota
Abstract: The present study aimed at investigating the immediate and delayed effects of a multiple-strategy instruction on English as a Foreign Language (EFL) learners' reading performance. The sample of the study consisted of 99, 11–12 year old, Greek-speaking EFL learners. The study, quasi experimental in design, involved an experimental group that received a three-month strategy instruction set within the Direct Explanation framework and a control group that received no such training but participated in the pretest, immediate and delayed posttest measurements. The results of the study indicated that the students in the experimental group improved their reading performance both in the immediate and delayed posttest measurements as compared to the students in the control group. Empirical evidence is provided regarding the effectiveness of explicit multiple-strategy training in EFL contexts with young, school-aged students. Educational implications and recommendations for further research are also discussed.